2004
DOI: 10.1103/physreva.70.022309
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishability of complete and unextendible product bases

Abstract: It is not always possible to distinguish multipartite orthogonal states if only local operation and classical communication (LOCC) are allowed. We prove that we cannot distinguish the states of an unextendible product basis (UPB) by LOCC even when infinite resources (infinite-dimensional ancillas, infinite number of operations). Moreover we give a necessary and sufficient condition for the LOCC distinguishability of complete product bases.Comment: added necessary and sufficient condition for complete product b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
76
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 17 publications
1
76
0
Order By: Relevance
“…Recently, there has been a renewed wave of interest in LOCC alongside new discoveries concerning asymptotic resources in LOCC processing [Rin04,Chi11,KKB11,CLMO12]. It has now been shown that when an unbounded number of communication rounds are allowed, or when a particular task needs only to be accomplished with an arbitrarily small failure rate (but not perfectly), more can be accomplished than in the setting of finite rounds and perfect success rates.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a renewed wave of interest in LOCC alongside new discoveries concerning asymptotic resources in LOCC processing [Rin04,Chi11,KKB11,CLMO12]. It has now been shown that when an unbounded number of communication rounds are allowed, or when a particular task needs only to be accomplished with an arbitrarily small failure rate (but not perfectly), more can be accomplished than in the setting of finite rounds and perfect success rates.…”
Section: Introductionmentioning
confidence: 99%
“…The attempt at a characterization of GESs made by us in [8] was qualitative, in a sense that we have only considered the problem of their general constructions in setups with an arbitrary number of parties holding subsystems of arbitrary local dimensions (see [19] for recent advances). This has been linked with the notion of the unextendible product bases [20], another very powerful tool with diverse applications (see, e.g., [21][22][23]). Clearly, however, the quantitative description of GESs (or, more generally, any subspaces) is also vital, as it provides a means of comparing them and potentially deciding on their usefulness in certain tasks.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the set of UPB constitutes a special class of locally indistinguishable product states [16,30]. So it is interesting to ask whether there are some other classes of locally indistinguishable orthogonal product states except the UPB.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them considered the set with maximally entangled states [5][6][7][8][9][10][11][12][13][14], while the others aimed at the set with product states [2,[15][16][17][18][19][20][21][22][23][24][25][26]. Both of these researches can lead us a better understanding the limitation of the local operations and classical communication.…”
Section: Introductionmentioning
confidence: 99%